Social Dynamics in the Preservation of the Incung Script: A Sociological Study of the Role of the Jambi Community in Maintaining the Cultural Heritage of the Kerinci Tribe - Oksa Putra, M. Zikril; Nurcahya, Yan; Kautsar Thariq Syah, Muhammad; Sugiarto, Deri; Hafiy Bin Abdul Rashid, Muhammad (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study aims to analyze the social dynamics in the preservation of the Incung script among the Kerinci community in Jambi Province amidst cultural changes and modernization, as well as explore the strategies employed by the community and local institutions to ensure its sustainability. The research method used is a qualitative approach with data collection techniques including in-depth interviews, participatory observation, and document analysis related to cultural preservation policies. The findings indicate that although customary communities and local educational institutions still teach the Incung script, the declining interest among the younger generation is attributed to the dominance of the Latin script and the development of digital technology. However, various preservation efforts have been implemented, such as teaching the Incung script in schools, creating digital fonts, and integrating it into batik art and local cultural products. This study contributes to the understanding of the preservation of traditional scripts in the context of modernization and provides insights for the development of more relevant cultural policies for younger generations.